Kegiatan Kampus Mengajar dalam Meningkatkan Keterampilan Literasidan Numerasi Siswa Sekolah Dasar - wildaniah, Ragil (Cahaya Smart Nusantara, 2023)
The Teaching Campus Program Batch 4 which is a form of implementation of Merdeka Learn Kampus Merdeka (MBKM) in the form of teaching assistance to empower students in assisting the learning process in elementary schools in various villages/cities, one of which is SD Negeri 1 Parakan which is located in Samarang District , Garut Regency, West Java Province . In this program, students who are involved have the responsibility of assisting the school in the teaching process (Numeration and Literacy), assisting with technology adaptation, and assisting with administration. In addition, students have a responsibility to improve the character of students and increase students' interest in learning. The results of this program are to inculcate empathy and social sensitivity in students towards the problems of people's lives around them; hone thinking skills in working together across fields of knowledge and diverse origins of students in solving problems encountered; develop student insight, character and Soft Skills; encouraging and spurring national development by fostering people's motivation to participate in development; as well as increasing the role and real contribution of universities and students in national development.